Pro .NET 2.0 Extreme Programming - Pearman, Greg; Goodwill, James (Apress : Imprint: Apress, 2006)
While other extreme programming (XP) books are usually theoretical in approach, this book steers you through the practical application of extreme programming with code-level solutions. So if you're currently a .NET 1.1 (or future .NET 2.0) developer, and need to put XP into practice, pick up this book. You will learn how to apply XP principles in a real-world environment. This book provides an in-depth look at each of the XP practices and examines how each of these fits into the project development life cycle. Thus, by showing you how to work with .NET 1.1 today, and .NET 2.0 tomorrow, this book bestows you with long-term vision for extreme programming with Microsoft technologies.